PENGEMBANGAN PERANGKAT PEMBELAJARAN FISIKA DENGAN STRATEGI ICE BREAKER UNTUK MENINGKATKAN MOTIVASI BELAJAR FISIKA PADA MATERI ELASTISITAS DAN HUKUM HOOKE KELAS XI SMA - Khairy, Hijraturrahma; Zulirfan, Zulirfan; Fakhruddin, Fakhruddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to produce a physics learning tool with an ice breaking strategy that is valid for use in physics learning for class XI SMA on the subject of Elasticity and Hooke's Law. The integration of the ice breaking strategy in physics learning is expected to make physics lessons less boring for students, especially if students learn during the afternoon study hours. This R & D research uses the ADDIE development model. The learning tools developed include: RPP, LKPD, and Cognitive Learning Outcomes Test for Elasticity and Hooke's Law. The results of the expert validation process show that the physics learning device using the ice breaking strategy developed has been declared valid with an average score of 3.44 with a maximum scale of 4. Thus, physics learning tools that integrate the ice breaking strategy are declared feasible to be used to teach material Elasticity and Hooke's Law for class XI SMA.Key Words: Physics Learning Tools, Ice Breaking Strategy,Elasticity and Hooke's Law.